Endoplasmic reticulum stress protein GRP78 modulates lipid metabolism to control drug sensitivity and anti-tumor immunity in breast cancer - Cook, Katherine L. (Cancer Res, 2016)
The unfolded protein response is an endoplasmic reticulum stress pathway mediated by the protein chaperone glucose regulated-protein 78 (GRP78). Metabolic analysis of breast cancer cells shows that GRP78 silencing increases the intracellular concentrations of essential polyunsaturated fats including linoleic acid. Accumulation of fatty acids is due to an inhibition of mitochondrial fatty acid transport, resulting in a reduction of fatty acid oxidation. These data suggest a novel role of GRP78 mediating cellular metabolism. We validated the effect of GRP78-regulated metabolite changes by treating tumor-bearing mice with tamoxifen and/or linoleic acid. Tumors treated with linoleic acid plus tamoxifen exhibited reduced tumor area and tumor weight. Inhibition of either GRP78 or linoleic acid treatment increased MCP-1 serum levels, decreased CD47 expression, and increased macrophage infiltration, suggesting a novel role for GRP78 in regulating innate immunity. GRP78 control of fatty acid oxidation may represent a new homeostatic function for GRP78.